Entrer à l'école maternelle : le contrat narcissique à l'épreuve du scolaire - Véronique Kannengiesser
This article focuses on the separation generated by entry into the infant school. This necessary separation is analysed as source of an anguish not only for the child but also for his family. A strong hypothesis is that the unprecedented meeting for the child with the school form participates of this anguish. The article, based on authors historians and sociologists of the education, shows that the infant school, since its creation, distinguishes itself of the other childcare facilities and that its educational model tends increasingly towards that of the elementary school but with its own objectives. According to a clinical approach of psychoanalytic orientation, fed by observations of classes and unstructured interviews with teachers, one of the psychic stakes in the separation during the first schooling is analysed: the narcissistic contract which allows the subject to emancipate and to take a place in the social group.